Towards a 'Social Anthropology' of End-of-Life Moral Deliberation: A Study of Australian Salvation Army Officers. (August 2020) - Cameron, Andrew; Stevens, Bruce; Shaw, Rhonda; Bewert, Peter; Salt, Mavis; Ma, Jennifer
A research project by the Schools of Theology and Psychology of Australia's Charles Sturt University surveyed a large sample of Salvation Army officers. This article considers survey responses to two questions relating to end-of-life care: the use of pain medications that may shorten life, and the cessation of fluid and food intake. The results of the analyses are evaluated in terms of Michael Banner's proposal that moral theology should more assiduously converse with 'patient ethnographic study', which the survey instantiates to some extent. Banner's proposal and the results of the survey are contrasted to Peter Singer's analytical moral philosophical dictums on end-of-life care. The results are also compared to a metastudy by Andrea Rodríguez-Prat and Evert van Leeuwen of 14 ethnographic studies of those who wish to hasten death at the end of life. We conclude that respondents exemplify a form of moral reasoning that is embedded within Christian spirituality; counters the assumptions of Singer's approach; contrasts the diminishment of 'meaning' at the end of life, as seen in Rodríguez-Prat and van Leeuwen; and deserves further respectful ethnographic study.